2000
DOI: 10.1902/jop.2000.71.7.1130
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Genetic Variation on the Splenic T Cell Cytokine and Specific Serum Antibody Responses to Porphyromonas gingivalis in Mice

Abstract: This study has shown that genetic differences at the level of H-2 haplotype induce variations in the local and T and B cell responses to P. gingivalis antigens. The responses of DBA/2J mice which have the same haplotype as BALB/c mice suggest that factors other than H-2 haplotype such as the C5 deficiency may influence this immune response. The significance of the specific antibody and T cell responses and of their inverse relationship to susceptibility to periodontal disease remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
2
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 21 publications
8
32
2
1
Order By: Relevance
“…The results of the present study have demonstrated that in general the percentages of cytokine-positive CD8 cells in the spleens of immunized mice were significantly higher than those of the CD4 cells, as has been reported previously [27,28]. Also, while the percentages of cytokine positive CD8 cells were increased for the most part compared with the control group, only the percentage of IL-4 + CD4 cells was increased in the two groups immunized with both F. nucleatum and P. gingivalis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of the present study have demonstrated that in general the percentages of cytokine-positive CD8 cells in the spleens of immunized mice were significantly higher than those of the CD4 cells, as has been reported previously [27,28]. Also, while the percentages of cytokine positive CD8 cells were increased for the most part compared with the control group, only the percentage of IL-4 + CD4 cells was increased in the two groups immunized with both F. nucleatum and P. gingivalis.…”
Section: Discussionsupporting
confidence: 90%
“…Following on from this study, Ebersole et al [19] showed that active immunization of mice with P. gingivalis protected against challenge with P. gingivalis as well as P. gingivalis together with F. nucleatum and this protection in terms of lesion size, correlated with the levels of specific serum IgG antibody. This has also been demonstrated in another study, in which strains of mice demonstrating a faster healing pattern of lesions after challenge with P. gingivalis had higher serum anti-P. gingivalis antibody levels than those strains which had slower healing lesions [27].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…They have roles in the function and differentiation of T cells, and they designate the T-helper subsets to amplify or control the amplitude of the inflammation and the destruction related to inflammation (2,3). The macrophages and T cells are dominate in the early/stable lesions of chronic periodontitis (CP), leading to the consideration that this response is developed by the Th1 cytokines.…”
Section: Introductionmentioning
confidence: 99%